Pengembangan, Implementasi, dan Pelatihan Penggunaan Website Absensi Prakerin untuk Meningkatkan Efisiensi dan Efektivitas Pengelolaan Absensi di SMK Assanadiyah Palembang - Febriyanti Panjaitan; Usman Ependi; Ari Muzakir; Hamim Tezar Rizandi; Muhammad Ridho Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This project aims to develop and implement an attendance website for Prakerin (Industrial Work Practice) at SMK Assanadiyah Palembang to improve the efficiency and effectiveness of managing student attendance during the Prakerin program. The use of information technology is expected to facilitate monitoring. The methods used include needs analysis, system design and development, implementation and testing, training and guidance, and evaluation and improvement. The results of this project show that key features such as the attendance dashboard, daily reports, and attendance recapitulation facilitate teachers and supervisors in monitoring student attendance. Additionally, more structured student data management and comprehensive reports and analysis enable better evaluation of the Prakerin program. Evaluation of training performance through pretest and posttest with five users representing teachers, students, and field supervisors showed a significant improvement in understanding and skills in using the website, with an average pretest score of 70.78% and an average posttest score of 89.08%. The training and technical support provided ensure that users can utilize the system optimally. In conclusion, the implementation of this Prakerin attendance website has successfully improved the efficiency and effectiveness of educational management at SMK Assanadiyah Palembang.